Prospective and Occupational Expectations Fishworkers of Ecuador to Change Matrix Production Country - Pazmiño Solys, Gabriel Arturo (2016)
This article presents a forward-looking approach to occupational mobility of artisanal fishermen from Ecuador to changing the productive matrix of the country and the improvement of working conditions in their craft piques ports, through a quantitative analysis of their aspirations and occupational expectations. The methodology to be considered is the use of secondary data collected through a survey administered to 392 fishermen in the five major artisanal fishing ports of Ecuador, Puerto Aconcito and Santa Rosa in the province of Santa Elena, Puerto Jaramijo and the San Mateo Manabí province and Puerto La Poza of the Province of Esmeraldas. The results indicate that there is an element of identity that defines the guidelines for the ocupacionalidad of fishermen in terms of their occupational aspirations and expectations that fishermen cast for themselves and their children. At a subjective level, the traditional dimension of the office of Fish workers exemplified the importance of work as constituent axis of the identity of individuals, permanence in the sector, in the intergenerational transmission of the trade, in the creation of family businesses around fishing and the refusal to change occupations.